Estrategias metodológicas y su influencia en la construcción de polígonos regulares e irregulares en la asignatura dibujo técnico aplicado en los estudiantes del 3er año de bachillerato del colegio nacional técnico Kléber Franco Cruz de la ciudad de Machala provincia de El Oro periodo lectivo 2014 - 2015 - Arboleda Hurtado, Dalton Jefferson (2015)
The development of this thesis, Methodological strategies and their influence on the construction of regular and irregular polygons in the technical design applied in the 3rd year students of technical high school national school Kléber Franco Cruz city of Machala province of the subject Gold academic year 2014 - 2015, is a research project aimed at determining how are the methodological strategy used by teachers in regular and irregular construction in the 3rd year of high school polygons, for which a methodological process based on inductive, deductive, descriptive statistical methods and hypothetical, the same as those supported in the techniques of observation, interviews and survey was developed.